Contemporary Africa's Growth and Development: Issues, Paradox and Solutions - Attah-Poku, Agyemang (Hamilton Books, 2012)
This book examines the various factors that have influenced the growth and development process of contemporary Africa. After discussing and weighing the schools of thought that have attempted to explain the paradox of Africa’s reduced growth and development in the midst of abundant resources, this volume comes up with comprehensive and detailed suggestions and recommendations to address this painful experience. This book consistently states that the average Africans, forming the overwhelming majority of the African population, are the least, if at all, to be blamed for the paradox; but rather the African leadership and its external cronies are to be fully blamed. Contemporary Africa’s Growth and Development seeks a solution to the African growth and development puzzle in proper allocation and oversight of resources, vision, perseverance, courage, corruption-free and good governance, as well as concrete, provable, solid, and genuine unity.